Upaya Meningkatkan Minat dan Hasil Belajar Siswa Kelas IIII melalui Model Pembelajaran Numbered Heads Together Pada Mata Pelajaran Matematika di SDN Perwira II Bekasi Utara - Arrahim Arrahim; Nurul Oktavia (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This study aims to increase the interest and learning outcomes of class III students through a joint head-numbered learning model on mathematics subjects at North Bekasi Second Elementary School. This type of research uses Classroom Action Research which consists of 2 cycles. Backpack subject 23 students. Data collection techniques consist of observation sheets and essay tests.Based on research, interest in the first cycle obtained an average value of 76.45 with a percentage of 73.91% and the second cycle obtained an average of 86.96 with a percentage of 86.96%. Then, the learning outcomes in the first cycle obtained an average value of 74.18 with a percentage of completeness of 69.57% and the second cycle obtained an average value of 86.96 with a percentage of completeness of 82.61%. This shows that the Numbered Heads Together model can increase the interest and learning outcomes of class III students in Mathematics at North Bekasi Second Elementary School.